Dynamic characterization of vehicle structural panels - Hanouf, Zahir; Faris, Waleed Fekry; Mohd Nor, Mohd Jailani (Inderscience Publishers, 2015)
The dynamic characterisation of vehicle structures is a crucial step in NVH analysis and helps in refining the vibration and noise in new vehicles, which is becoming a marketing edge as well. This paper investigates the dynamic properties of two parts of the vehicle structure which are door and hood panels. Theoretical modal analysis, which is referred to as finite element analysis (FEA) and experimental modal analysis (EMA) or modal testing, has been used as investigative tools. The paper investigates the structural dynamic properties of door and hood panels of a local car. ME’scpe software was used to analyse the data obtained from the Pulse to extract the dynamic properties of the panels. Ls-dyna software was used to analyse the dynamic behaviour of the structure. The comparison between the results obtained from both analyses showed some similarity in frequencies and mode shapes. Finally the paper concludes that experimental modal analysis and finite element analysis can both be used to extract dynamic properties of structures.